Choosing drugs for the treatment of diabetic neuropathy. (August 2015) - Alabdali, Majed; Qrimli, Mohammad; Barnett, Carolina; Abraham, Alon; Breiner, Ari; Katzberg, Hans D; Aljaafari, Danah; Albulaihe, Hana; Perkins, Bruce A; Bril, Vera
<x xml:space="preserve">Abstract</x> Introduction: Diabetic sensorimotor polyneuropathy (DSP) affects 50% of diabetes patients and is painful in about 26%. Although disease-modifying therapies are not available for DSP, symptomatic treatments for painful diabetic neuropathy (PDN) are effective. Areas covered: We performed a MEDLINE search on PubMed using the search terms: treatment diabetic neuropathy and treatment PDN. This review outlines the problem posed by DSP, the clinical presentation and the characterization of PDN. A discussion of disease-modifying interventions, including the benefits of strict glycemic control, is followed by a focus on interventions for PDN including antidepressants, anticonvulsants and other treatments. Expert opinion: Disease modification in DSP remains an unmet need in clinical medicine affecting a large percentage of the population with concomitant healthcare costs. Strict glycemic control and attention to potential risk factors such as hypertension, hyperlipidemia and obesity may minimize DSP. Many patients benefit from treatment of their painful symptoms with anticonvulsants or antidepressants, but all are associated with significant side effects that limit their usefulness. There is a need for treatments of PDN with fewer side effects and more effective pain relief.